11 Evaluation of delivery analysis software (Accuray), comparison to Delta 4 Phantom. (December 2018) - Fontaine, J.; Taecsh, F.; Djibo-Sidikou, A.; Bertosi, A.; Retif, P.
Abstract : Introduction: Delivery Analysis software uses the signal received from xenon detectors of Tomotherapy to calculate the MLC leafs open time (LOTs) and compares the measured sinogram with the planned one. We have used Delivery analysis for Tomotherapy pretreatments controls for more than two years. Each measure was also carried out using the Delta 4 phantom. In this study, we propose a comparison of these two measurement tools. Methods: First, an evaluation of the repeatability and the reproducibility of both tools was realized.Then, a retrospective study of the results obtained for 82 patients, regardless the localization, was led. The percentages of points passing the gamma index criterion 3 %-3 mm with a 10 % threshold were analyzed according to the detector type as well as treatments plans parameters. Finally, a set of measures of deliberately modified plans was realized on the Delta 4 in order to test a potential dependence of the results with the gantry period. To achieve this, nine plans were created from the same MLC sequencing by modifying the period of rotation between 11 s and 30 s while keeping the same LOTs. Results: The repeatability and the reproducibility of Delivery Analysis software were respectively 0.06% and 0.51% versus 0.43% and 0.92% for the Delta 4. The retrospective study did not make it possible to highlight a correlation between the results obtained with the Delta 4 and Delivery Analysis. However, concerning the Delivery Analysis and looking at the treatments plans parameters, we observed a strong correlation of the percentage between points passing the gamma criterion and the gantry period which was not visible with the Delta 4 (Fig. 1). Measurements made for different gantry periods with the Delta 4 seemed to confirm that there was no correlation between the performances of the machine and the gantry period. Indeed, a decrease of only 2 % of the percentage of points crossing the criteria gamma was noticed for gantry periods ranging from 30 s to 11 s. Conclusions: Using Delivery Analysis software for pretreatments quality controls could be very interesting to save time. Furthermore, they could be done with a better repeatability/ reproducibility of measurements than with the Delta 4. However, the results obtained with the software are difficult to correlate to those obtained with the Delta 4 phantom. In addition, they seem abnormally correlated to the gantry period. These results should be confirmed with further experiments.